ZAHIRIDDIN MUHAMMAD BABUR: MULTIFACETED PHILOSOPHY AND LITERARY TALENT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article explores the works of Zahiriddin Muhammad Babur, focusing on his unique philosophical perspectives and thoughts on society. Babur is recognized not only as a prominent ruler and military leader but also for his intellectual and literary contributions, as well as his deep reflections on human nature and society. The study particularly examines how his works, especially the Baburnama and his poetry, address themes such as human nature, life’s purpose, justice, love, and the value of humanity. Babur’s philosophical views and creations remain highly relevant for contemporary society.